Liquid chromatography-mass spectrometry analysis and phytochemical screening of trimad: an ayurvedic Polyherbal formulation - SURESH P KHADKE,; ANIKET A KUVALEKAR, (International Journal of Pharma and Bio Sciences, 2018)
Trimad is a polyherbal formulation mentioned in Ayurvedic literature. The formulation is a composite mixture of three plant parts including rhizomes of Nagarmotha (Cyperus rotandus L.), fruits of Vidang (Embelia ribes Burm.) and root of Chitrak (Plumbago zylenica L.). The present study was undertaken to evaluate phytochemical constituents of Trimad polyherbal formulation through Liquid Chromatography-Mass Spectrometry (LC-MS) analysis. Chromatographic conditions for separation are as follows: The mobile phase was a combination of solvents: water (0.1% formic acid) (A) and Acetonitrile (B). The flow rate was 0.35mL/min. The gradient begins at 2% B and reached 98% B by 12 min. Consequently, the mixture returned to 2% B for a 3 min re-equilibration period. The components were subjected to the mass analyzer through electrospray ionization probe operating in positive and negative mode with the following conditions: capillary voltage for negative and positive, 2500, 4000V; fragmentor voltage, 150V; source temperature, 325°C; sheath gas temperature, 295°C; nebulizer pressure, 45 PSI; and gas flow, 8 L/min. Total twenty putative compounds were identified from methanolic extract of Trimad. Negative and Positive ionization mode detected around 17 and 12 compounds respectively. Out of which, nine compounds are detected in both ionization mode. In negative ionization mode, β-glucopyranosyl plumbagic acid; xanthyletin; embelin; sugeonyl acetate; 1-tetradecene; cyclopentadecane; tetracosanoic acid methyl ester and tricosanoic acid methyl ester compounds were detected. In positive ionization mode, rotundines; γ –muurolene and ethyl p methoxycinnamate were identified. Nine compounds such as cyperol; β- asarone; oleic acid; campholaldehyde; thymol; 1-epineo-isoshinanolone; α-cyperone; phenol 2,4- bis(1,1-dimethylethyl) and n-hexadecanoic acid were detected in both ionization modes. Probably, this is the first report of high-throughput screening of Trimad phytoconstituents through LC-MS analysis. Further studies can examine the mechanisms of action of this formulation.